2003
DOI: 10.1073/pnas.2634884100
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determinants of amyloid fibril formation

Abstract: The establishment of rules that link sequence and amyloid feature is critical for our understanding of misfolding diseases. To this end, we have performed a saturation mutagenesis analysis on the de novodesigned amyloid peptide STVIIE (1). The positional scanning mutagenesis has revealed that there is a position dependence on mutation of amyloid fibril formation and that both very tolerant and restrictive positions to mutation can be found within an amyloid sequence. In this system, mutations that accelerate ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
362
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(390 citation statements)
references
References 42 publications
20
362
2
Order By: Relevance
“…27,32 Serrano and coworkers have also identified common patterns among amyloidogenic peptides by using mutation scanning experiments. 33 The X 1 X 2 V 3 I 4 I 5 X 6 pattern found in their experiments corresponds well with our computed sequence features of the class 7 topology.…”
Section: Cc-by-nc 40 International License Peer-reviewed) Is the Autsupporting
confidence: 83%
“…27,32 Serrano and coworkers have also identified common patterns among amyloidogenic peptides by using mutation scanning experiments. 33 The X 1 X 2 V 3 I 4 I 5 X 6 pattern found in their experiments corresponds well with our computed sequence features of the class 7 topology.…”
Section: Cc-by-nc 40 International License Peer-reviewed) Is the Autsupporting
confidence: 83%
“…Short oligopeptide repeat sequences that reside within the PrDs also have role in the conformational plasticity. [123][124][125] Shuffled sequences of aminoacids from yeast prion domains remain capable of forming amyloids in vitro, indicating that the amino acid composition of prion domains, rather than their sequence alone, contributes importantly to amyloid assembly. 126 Recently synthetic prions have been made de novo enabled by the development of computer algorithms like PAPA (Prion Aggregation Prediction Algorithm) that uses amino acid composition to predict prion propensities of intrinsically disordered protein domains.…”
Section: Characterization Of Prions and Prion Domainsmentioning
confidence: 99%
“…6,7 DuBay et al found hydrophobicity to exhibit the strongest correlation with the aggregation rates among parameters tested in regression analysis. 45 Hydrophobic amino acids are consistently ranked high for cross-β aggregation in systematic mutation studies by Lopez de la Paz et al 6,50 The importance of hydrophobicity is generally interpreted as the driving force for β-sheet lamination that creates a "dry interface" between adjacent β-sheets. 51 Our finding of the dominant role of nonpolar surface burial for single-layer β-sheet stability suggest that nonpolar surface burial is also critical for the formation of each layer of β-sheets.…”
Section: Implications For β-Sheet Protein Design and β-Rich Peptide Smentioning
confidence: 99%